The Relationship between Health Control Behavior and Compliance with Medication in Pulmonary Tuberculosis Patients at the Jember Lung Hospital - Cahyani Maulida, Savira; Suryaningsih, Yeni; Komarudin (Universitas Bondowoso, 2024)
Background: Compliance is often a problem in patients with chronic diseases that require lifestyle modification and long-term treatment such as pulmonary tuberculosis. Patient compliance behavior in treatment can be influenced by psychological factors such as memory and health control behavior. Each individual has different behavior regarding the extent of their current health condition and is determined by their own behavior (internal) or by external forces. This states that health control behavior greatly determines the decisions taken by patients regarding health conditions and compliance with treatment Method: This study used a correlational design which aimed to reveal the relationship between health control behavior and medication adherence in pulmonary tuberculosis patients at the Jember Lung Hospital and used a cross sectional approach. The population in this study were pulmonary tuberculosis patients who underwent treatment at the Pulmonary Tuberculosis Clinic, Jember Lung Hospital with a sample of 82 respondents. The sampling technique uses total sampling. Result: The results of research using the Spearman Rho Test obtained a p value of 0.001, where if this value is compared with the ɑ value, it shows a p value <ɑ, namely 0.001 < 0.05, which means there is a relationship between health control behavior and adherence to taking medication in pulmonary tuberculosis patients in Jember Lung Hospital with a calculated r of 0.478 in the sufficient correlation category and the direction of the correlation is positive, which means that the better a person's health control behavior, the more compliant a person will be in taking medication. Conclusion: This research can provide input to nursing services regarding the importance of health control behavior with medication adherence in pulmonary tuberculosis patients. This can be done by nurses to provide motivation by providing education to pulmonary tuberculosis patients so that they have good health control behavior and are compliant in taking medication.